Experimental Evidence of the Benefits of Acupuncture for Alzheimer's Disease: An Updated Review - Yu, Chao-Chao; Du, Yan-Jun; Wang, Shu-Qin; Liu, Le-Bin; Shen, Feng; Wang, Li; Lin, Yuan-Fang; Kong, Li-Hong (Frontiers in Neuroscience, 2020)
As the global population ages, the prevalence of Alzheimer’s disease (AD), the most common form of dementia, is also increasing. At present, there are no widely recognized drugs able to ameliorate the cognitive dysfunction caused by AD. The failure of several promising clinical trials in recent years has highlighted the urgent need for novel strategies to both prevent and treat AD. Notably, a growing body of literature supports the efficacy of acupuncture for AD. In this review, we summarize the previously reported mechanisms of acupuncture’s beneficial effects in AD, including the ability of acupuncture to modulate Aβ metabolism, tau phosphorylation, neurotransmitters, neurogenesis, synapse and neuron function, autophagy, neuronal apoptosis, neuroinflammation, cerebral glucose metabolism, and brain responses. Taken together, these findings suggest that acupuncture provides therapeutic effects for AD.